Evaluation of the antidyslipidemic and nephroprotective effect of methanolic seed extract of Lepidium sativum on male Swiss albino mice fed on deep fried palm oil - Ahmed, Ebsa Tofik; Dukessa, Abebe; Mateos, Tigist; Meka, Welela; Seyoum Moti, Meskelu; Zawdie, Belay (Frontiers in Nutrition, 2025)
IntroductionCurrently, there is dramatic change in dietary habits. Consumption of energy dense foods are becoming common practice globally. Increased consumption of energy dense foods are main cause of disorder on lipid metabolism and kidney function, which are primary risk factors for many chronic diseases. Thus, this study aims to evaluate antidyslipidemic and nephroprotective effect of methanolic seed extract of Lepidium sativum (MSELS) on mice fed on deep fried palm oil.MethodsThe study carried out using 24 mice that grouped into four groups. G-I fed on normal mice pellets and distilled water. G- II fed on deep fried palm oil and distilled water. G-III and IV fed on deep fried palm oil and treated with MSELS of 200 and 400 mg/ kg/day, respectively. Each group treated per orally for 8 weeks. At the end of study, mice fasted overnight, anesthetized and blood taken by cardiac puncture for lipid profile and kidney parameters. Then, sacrificed by cervical dislocation, liver and kidney tissues taken for histopathology investigation.Result and DiscussionThe serum total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels decreased while high density lipoprotein cholesterol (HDL-C) increased significantly in G- IV only whereas serum LDL-C/HDL-C ratio and creatinine levels showed a significant decrement in both G- III and IV when compared with G- II. The serum blood urea nitrogen (BUN) and uric acid levels decreased in G- III and IV even though only serum uric acid value in G-IV decreased significantly when compared with G-II. Besides, G-IV showed significant reduction in liver weight as well as restoration of liver and kidney histopathology when compared with G- II than G-III.ConclusionBased on the above results, MSELS showed better antidyslipidemic and nephroprotective effect on male mice treated with deep fried palm oil at the dose of 400 mg/kg/day of MSELS.